1991
DOI: 10.1021/ef00025a002
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum pyrolysis mass spectrometry of Pittsburgh No. 8 coal: comparison of three different, time-resolved techniques

Abstract: Three different vacuum pyrolysis mass spectrometry techniques, viz., pyrolysis-field ionization mass spectrometry, thermogravimetry/low voltage electron ionization mass spectrometry, and Curie-point pyrolysis-low voltage electron ionization mass spectrometry, were used to analyze samples of Pittsburgh No. 8 coal obtained from the Argonne National Laboratory Premium Coal Sample Program. The primary objective was to assess the effects of differences in experimental techniques and conditions, e.g., with regard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A higher temperature ramp rate did not allow time for the PAH molecular weight 178 (phenanthrene and anthracene) to show a desorption curve on a consistent basis with some of the materials tested. A shift toward higher peak temperatures for desorption response with increased heating rate has been described by Yun and Meuzelaar (1991). In that case, the PAH could be released at a slightly elevated temperature because there maybe insufficient time for temperature equilibration.…”
Section: Methods Developmentmentioning
confidence: 87%
See 2 more Smart Citations
“…A higher temperature ramp rate did not allow time for the PAH molecular weight 178 (phenanthrene and anthracene) to show a desorption curve on a consistent basis with some of the materials tested. A shift toward higher peak temperatures for desorption response with increased heating rate has been described by Yun and Meuzelaar (1991). In that case, the PAH could be released at a slightly elevated temperature because there maybe insufficient time for temperature equilibration.…”
Section: Methods Developmentmentioning
confidence: 87%
“…Various adaptations of thermal program desorption (TPD) techniques have been used in the past to study: desorption of gases from solid surfaces (Falconer and Madix, 1975;King, 1975), desorption of toluene from kaolin pellets (Keys and Silcox, 1994), pyrolysis of hydrocarbons from coal (Yun and Meuzelaar, 1991), estimation of PAH vapor pressures (Oja and Suuberg, 1997;Tesconi and Yalkowski, 1998), and desorption activation energies of trichloroethylene from silica gel (Farrell et al, 1999). Thermal desorption techniques have also been explored for their utility in detecting and quantifying organic contaminants in soil samples (Robbat et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several reviews, this extended research area has been summarized (4, [120][121][122][123]. Major areas of interest are fossil biomaterials such as coals, kerogens, bitumen and asphaltenes (11,77,78,120,(123)(124)(125)(126)(127)(128), and oil shales (122,125). Materials of recent geological history such as peat (129,130), soil humic acids, and soil organic matter (131)(132)(133) have also been investigated (134)(135)(136).…”
Section: Geochemical and Environmental Applicationsmentioning
confidence: 99%
“…Structural changes such as macromolecular relaxation and thermoplastic transitions in coal organic matters at temperature lower than 500 °C are important from the view of their utilization processes such as carbonization, gasification, liquefaction, and combustion. Studies based on 1 H NMR, , pyrolysis−mass spectrometry, , and field ionization mass spectrometry , have strongly suggested that a fundamentally different process is occurring at the low-temperature region in contrast to the ensuing pyrolytic process involving chemical decomposition. The committee for New Concepts on Coal Carbonization Control for Coke Production, the Iron and Steel Institute of Japan, has recently proposed a novel method comprising rapid preheating of coal up to around 450 °C and subsequent carbonization of coal softened.…”
Section: Introductionmentioning
confidence: 99%